IMPLEMENTASI RESTORATIVE JUSTICE DALAM PENYELESAIAN TINDAK PIDANA KASUS BULLYING DI BLITAR (STUDI PUTUSAN NO : 449/ PID.SUS / 2012 / PN.BLT.) - Ahmedhio Rahmadhani; Cekli Setya Pratiwi (Musamus University, 2022)
Today, crimes committed by children are growing quite rapidly. Bullying is an activity carried out with the aim of cornering other people with condescending tones, making fun of to physical violence. The judicial process against children often causes stigmatization and adverse impacts on children, one of the weaknesses is that the laws and regulations do not prevent children from entering formal justice from an early age. The crime of bullying has caused a lot of harm and unrest, such as the case that occurred in Blitar which started with two children who were violent against their own friends (study of decision no: 449/ pid.sus/2012/pn. blt.). The case ended with the imposition of a crime against the Defendant, even though UUSPPA has stipulated that protection must be given to children, including children who commit criminal acts. This writing uses a type of empirical normative research, namely by explaining the regulations that apply in regulating restorative justice and its implementation in the City of Blitar as well as the judge's considerations in deciding criminal regulations no. 449/Pidsus/2012/PN.Blt. The results of the study indicate that the application of restoratice justice in Blitar has not been carried out optimally because of the legal factor itself and the culture of the people in the area. One example of the application of restorative justice that has not been optimal is Decision Number 499/Pidsus/2012/PN.Blt because the judge handed down a criminal decision even though the imposition of a crime was a last resort against a child before the law. However, the Blitar District Court has made efforts to optimize the application of restorative justice in Blitar, one of which is by providing socialization and introduction to the community